Optimalisasi Dan Pengembangan Transportasi Perkotaan Di Dki Jakarta - Maimunah, Siti; Kuswati, Atik S. (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
The purpose of this studtj is to identifiJ the various problems that caused bottlenecking marement ofpeople and vehicles in the Greater Jakarta area on the vertices of a strategic transport. By using themethod of transportation development strategtJ through the Transport Demand Management (IDM)and Transport Supply Management (TSM), each of which is prepared through the optimiZJltionapproadi and the development and amstruction of infrastructure networks and facilities is expectedto provide input in the formulation of development strategies in urban transportation major dties inIndonesia so that national transport polictj to get solutions that are comprehensive, sustai.nable andoriented in short term, medium term and long term. It also required the existence of network integrationservices and network infrastructure for delivery through the integration of route and schedule ofop?1'l1lion and arrangement of transportation fur the node to create a single F£amless service to serviceusers.Keywords: Urban Transportation, TDM, TSM